"Back to the future: Beta radiation to treat recurrent in‐stent restenosis". Issue 1 (18th January 2021) - Rodriguez‐Paz, Enrique; Heuser, Richard
Key Points: When a patient presents with restenosis and two layers of previously place drug eluting stents this is a true treatment dilemma for the interventionist. Beta radiation has proven its efficacy to decrease in‐stent restenosis compared to standard PCI. No drug‐coated balloons are currently available in the United States for treatment of in‐stent restenosis.